The Second Time Around? Polanyi and Today's Fascist Tendency - Sandbrook, Richard (Peace Magazine, 2017)
Discusses the relevance of Polanyi’s double movement in light of increasing support for far-right, authoritarian and neo-fascist movements in Europe and North America. The author quotes The Great Transformation on how fascism “was rooted in a market system that refused to function” (21), however, he chooses to center his analysis on an unpublished essay of Polanyi’s entitled “The Fascist Virus”. From this, he extrapolates that fascism operates like a disease within liberal capitalism, becoming lethal when tensions between capitalism and democracy hit crisis levels and unleashing itself into the body politic (20).
Peace Studies
Keywords: fascism; right-wing populism

Society Must Be Protected - Turner, Mandy (Journal of Corporate Citizenship, 2007)
The multiple ways in which multinational corporations, financial and commodity markets and global trade feed into today's civil wars have recently become a key policy concern of the international community. Over the past five years, a number of initiatives have been launched, aimed at controlling the trade in conflict goods, ensuring good resource governance, advocating corporate social responsibility and promoting conflict-sensitive business practices. This article assesses these initiatives through the lens of Karl Polanyi's conception of the 'double movement', i.e. that capitalism automatically provokes protectionist impulses. It assesses the spaces created by neoliberal globalisation for illicit economic activity and conflict entrepreneurs, the relationship between the economy and conflict, and initiatives aimed at reducing conflict 'triggers'. It concludes that, in addition to the tension between commodification and social protection, there is another tension at work: between those who call for tough mandatory policies and those who promote best-practice guidelines.
Peace Studies; Business Studies
Keywords: Polanyi; business and conflict; capital market; commodification; corporate social responsibility; corruption; international business enterprises; international trade; protectionism; sanctions; social protection; social responsibility of business

The role of the UN Millennium Declaration and of the World Economic and World Social Forum for Structural Change - Abrahamson, Hans (Conference Papers – International Studies Association, 2005)
Globalisation can in a polanyian sense be understood as a double movement. Societal reaction to the shortcomings of the corporate driven process of globalisation from above (the first movement) creates a counter movement from below (the second movement). The relations between different actors within the political landscape and the area of tensions between the two movements are characterised by the gramscian war of position and its power struggle over the hegemonic discourse. At times the constellation of political forces permits an institutionalised state of equilibrium built on converging interests between different social forces. During the Westphalia era with its nation-state project the social contract constituted the base for such an historic compromise. The end of the cold war and strengthened process of corporate globalisation has eroded the base for this social contract on a national level increasing development gaps not only between countries but also within countries. This paper addresses the question of room for manoeuvre for structural change in order to deal with present challenges within the Global Political Economy. It discusses how possibly the UN Millennium Declaration could be used in the ongoing discursive war of position between actors at the World Economic Forum in Davos (representing the first movement) and actors at the World Social Forum in Porto Alegre (representing the second movement) in order create a social base for a new social contract albeit on the global level. Such a discussion also illustrates present potential of these arenas in contributing to a future global political economy of peace and development.
Peace Studies; Development Studies
Keywords: United Nations; World Economic Forum; economics; forums (discussion & debate); globalization; hegemony; political science

Discourses on peace and development - Hettne, B. (Progress in Development Studies, 2001)
Assuming a close relationship between peace and development, this paper analyses a succession of schools of thought in development forming part of three distinct, historically contextualized development and security discourses: the industrialization imperative in the emerging state-system in nineteenth-century Europe, the international concern with global poverty in the bipolar post second world war world and the current meaning of development in a globalized and increasingly chaotic world. The third of these discourses contains major challenges for development theory. The discourses are related to great transformations in political economy, understood in Polanyian terms as tensions between market expansion and societal response.
Peace Studies; Development Studies
Keywords: conflict; development theory; discourse; economic development; market expansion; peace; peace - economic aspects; security